Persepsi dan Preferensi Pengunjung Terhadap Tata Fasilitas Wisata di Taman Hutan Raya Ngurah Rai, Bali - LAKSMI, A.A. AYU SRIYANI; GUNADI, I GUSTI ALIT; YUSIANA, LURY SEVITA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2013)
Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} ABSTRACT Perception and Preference of Visitors about the Setting of Tourism Facilities in Forest Park Ngurah Rai, Bali The condition of tourism facilities in forest park Ngurah Rai is not well organized. Based on this condition, perception and preference must be known to make facilities condition better. The aims of this research are to know the setting of facilities, perception and preference, also recommend the setting of tourism facilities. This research was done in Mangrove trail area in February-June 2012, with qualitative description method. The conclusions of this research are facilities condition is not well organized and cared. Visitors’ perceptions are uncomfortable, unsafe, and not really good view to see. The recommendation to be proposed is re-organizing based on comfort, safety, and beauty aspects. Keyword : perception, preference, governance tourist facilities, mangrove trail